Persepsi dan Preferensi Masyarakat terhadap Tingkat Kenyamanan Taman Merdeka Metro sebagai Ruang Interaksi Sosial di Masa Pandemi Covid-19 - Indah Nurrohimah; Indung Sitti Fatimah (Jurnal Lanskap Indonesia, 2022)
The covid-19 pandemic has resulted in changes in people's behavior, activities, and social space, thus triggering changes in the comfort level of visitors in the Merdeka Park area. This study aims to identify and analyze the comfort level of Merdeka Park as a social interaction space based on perceptions and preferences; and make recommendations for the design of Merdeka Park based on the results of the analysis of community perceptions and preferences. The analysis was used in this research are spatial analysis and descriptive analysis using quantitative and qualitative methods. Based on the results of the study, the comfort level of Merdeka Park is included in the very comfortable category as a social interaction space. The percentage of park comfort value is 84.1% which is generated from the average percentage of all parameters. The park's carrying capacity is 58 people per day with the addition of playing and sport rooms, as well as the addition of lawn facilities. The recommended design in this study is improving facilities, adding facilities, structuring vegetation, and adding vegetation.